Mutational analysis of the adenovirus E1a gene: the role of transcriptional regulation in transformation. - Schneider, J; Fisher, F; Goding, C; Jones, N (1987)
To determine whether the transcription regulatory activities of the adenoviral E1a gene play a role in its ability to transform primary cells we have constructed an extensive series of mutations within the E1a gene. The mutants have been characterized for their ability to transactivate the adenoviral early promoters, repress the transcriptional stimulation of the polyoma virus enhancer, establish primary baby rat kidney cells in culture and cooperate with the activated Ha-ras oncogene in morphologically transforming these cells. The mutant phenotypes reveal that: (i) the two transcription regulatory activities of E1a are separable since essential protein domains map within different regions of the protein; (ii) transactivation is unlikely to contribute significantly to E1a-mediated transformation since several isolated mutants lost the ability to transactivate but were nevertheless efficient at transformation; and (iii) both establishment and oncogene cooperation are linked to enhancer repression suggesting that E1a transforms cells by the repression of a cellular enhancer.